Water entrepreneurship can drive solar irrigation and climate mitigation in Nepal - Shrestha, Shisher; Gautam, K.; Neupane, Nilhari; Kuriachen, Philip; Fanaian, Safa (International Water Management Institute, 2025)
Small solar pumps help individual farmers, but larger systems that serve collective fields could drive uptake and lift rural incomes across Nepal’s breadbasket, as lessons from its neighbor Indian state of Bihar show.